(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate the anatomical and functional results in cases underwent 23-gauge pars plana vitrectomy (PPV) due to idiopathic stage 4 macular hole.Material and Methods: 17 eyes of 17 patients who underwent PPV due to idiopathic stage 4 macular hole between March 2013 and March 2016 at İnönü University Turgut Özal Medical Center Department of Ophthalmology were included in the study. The medical records of the patients were retrospectively reviewed. Macular hole staging was performed according to biomicroscopic examination and optical coherence tomography findings. Anatomical success was evaluated according to the condition of the macular hole after the surgery and functional success was evaluated according to the visual acuity.Results: 9 (53%) of the cases were females and 8 (47%) were males, the mean age was 66.6 ± 6.6 (55-81). PPV, internal limiting membrane (ILM) peeling and gas tamponade were applied to all cases. The mean follow-up period was 13.9±9.7 (4-30) months. ILM peeling was performed using trypan blue in three (17.6%) of the cases, brillant blue in 4 (23.5%) of the cases and membrane blue in 10 (58.8%) of the cases. Three cases (17.6%) were treated with C3F8 and 14 cases (82.3%) with SF6 gas tamponade. The mean preoperatively best-corrected visual acuity (BCVA) was 0.08±0.06 (0.03-0.2) and the mean postoperatively BCVA was 0.16±0.15 (0.03-0.5). Visual acuity did not change in two eyes (11.7%) and decreased in two eyes (11.7%). Macular hole had not closed in four patients (23.5%).Conclusion: 23 gauge PPV, ILM peeling and C3F8 or SF6 gas tamponade provides anatomical and functional success in the treatment of idiopathic stage 4 macular hole.Keywords: Internal limiting membrane; Macular hole; Pars plana vitrectomy.